Effect of Workload and Job Stress on Employee Turnover Intention: A Case Study of Higher Education Sector of Khyber Pakhtunkhwa - Dr. Nisar Muhammad; Dr. Anjum Ihsan; Dr. Kauser Hayat (Journal of Business & Tourism, 2021)
In present environment work load and stress at work is a significant and costly problem for various organization. On the other hand work force is considered the most valuable asset of an organization. One of the most important challenges for all the organization is on how to increase employees’ resistance level against job stress. The basic aim of the present research was to measure the effect of workload and job stress on employee turn over intention. The current study selected 245 respondents from various higher education institutions of Khyber pakhtunkhwa using stratified random sampling method. For the factorization of data exploratory and confirmatory factor analysis was done. The SEM technique was used to test hypotheses of the study with GFI, CFI, TLI, and RMSEA indices. The outcomes of the study show that workload and job-stress are correlated with employee turnover intention. Therefore, higher education institutions should develop appropriate strategies for the retention of their valuable employees.